Arctigenin inhibits RANKL‐induced osteoclastogenesis and hydroxyapatite resorption in vitro and prevents titanium particle–induced bone loss in vivo. Issue 4 (14th October 2018) - Wei, Gejin; Liang, Tihong; Wei, Chengming; Nong, Xiaolian; Lu, Qiteng; Zhao, Jinmin
Abstract: Wear particle–induced bone resorption leads to prosthesis loosening, which is a major complication associated with total joint arthroplasty. Although the exact mechanism remains unclear, wear particle–induced extensive osteoclastogenesis plays a critical role in this process. Thus, a potential treatment of prosthetic loosening is focused on suppressing extensive osteoclast formation and bone resorption, which prevents wear particle–induced osteolysis. Arctigenin isolated from Arctium lappa has numerous beneficial pharmacologic effects, including anti‐inflammatory, antiviral, and anticancer activities. Here, we explored the potential impact of arctigenin on titanium (Ti) particle–induced osteolysis in vivo. Our data showed that arctigenin significantly suppressed Ti particle–induced osteolysis and prevented bone destruction compared with Ti group. In addition, the number of osteoclasts reduced after treatment with arctigenin in vivo, indicating osteoclastogenesis might be inhibited by arctigenin. Next, bone marrow–derived macrophages were used to examine osteoclast differentiation, bone resorption, and activation of osteoclast‐related signaling pathways. The results showed that arctigenin inhibited RANKL‐induced osteoclastogenesis without any cytotoxicity and suppressed osteoclastic marker genes expression and hydroxyapatite resorption activity in a dose‐dependent manner. Additionally, arctigenin suppressed receptor activator of nuclear factor κΒ (NF‐κB) ligand–induced NF‐κB activation, concomitant with retarded IκBɑ degradation and inhibition of p65 nuclear translocation, leading to impaired osteoclastogenesis. Collectively, our results suggest that arctigenin is a promising candidate for the treatment of osteoclast‐related osteolytic diseases caused by excessive osteoclast formation. Abstract : 1. Arctigenin inhibited RANKL‐induced osteoclastogenesis without any cytotoxicity. 2. Arctigenin significantly suppressed titanium particle‐induced osteolysis and prevented bone destruction.